2022
DOI: 10.3390/su14159646
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Dairy Products: A Case Study of a Dairy Factory in Brazil

Abstract: The production of dairy products generates several environmental impacts, and life cycle assessment (LCA) is a useful methodology to quantify and understand those impacts. In Brazil, some traditional dairy products have not yet been evaluated using the LCA methodology. Based on this gap, we conducted a cradle-to-gate LCA of six dairy products from a plant in Minas Gerais, Brazil. We also performed two sensitivity analyses. The first analysis was on how the environmental profiles of the products changed dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…The CO 2 treatment effectively slowed down the increase of Firmicutes spoilage bacteria, but it did not have a high selectivity for Proteobacteria . The differences in the initial microbiota can be attributed to various factors such as bovine skin microflora, pasture‐raising environment, feed and agricultural equipment (Odeyemi et al ., 2020; dos Santos et al ., 2022; Pahalagedara et al ., 2023). Therefore, it is possible that changes in one or more of these aspects may contribute to observing a significantly different profile.…”
Section: Resultsmentioning
confidence: 99%
“…The CO 2 treatment effectively slowed down the increase of Firmicutes spoilage bacteria, but it did not have a high selectivity for Proteobacteria . The differences in the initial microbiota can be attributed to various factors such as bovine skin microflora, pasture‐raising environment, feed and agricultural equipment (Odeyemi et al ., 2020; dos Santos et al ., 2022; Pahalagedara et al ., 2023). Therefore, it is possible that changes in one or more of these aspects may contribute to observing a significantly different profile.…”
Section: Resultsmentioning
confidence: 99%
“…Buttermilk (BM) is another dairy by-product released by butter manufacturing. Estimating the environmental impact through a life cycle assessment methodology, it has been observed that BM does not influence the impact caused by the butter manufacturing process in as high a proportion as whey does in the cheese production process [19]. For many years, BM has been undervalued, although some studies carried out in the last decade have shown its potential, especially due to the proteins and lipids present in the milk fat globule membrane (MFGM) [20].…”
Section: Introductionmentioning
confidence: 99%